Puerarin inhibits vascular smooth muscle cells proliferation induced by fine particulate matter via suppressing of the p38 MAPK signaling pathway - Qiang Wan; Zhongyong Liu; Yuping Yang (BMC, 2018)
Abstract Background Fine particulate matter (PM2.5) is a major risk factor for the development and progression of atherosclerosis. Proliferation and infiltration of vascular smooth muscle cells (VSMCs) from the blood vessel media into the intima is a crucial step in the pathophysiology of atherosclerosis. Puerarin, a natural extract from Radix Puerariae, possesses significant anti-atherosclerosis properties. However, the underlying molecular mechanisms responsible for the effect of puerarin on the VSMCs proliferation induced by PM2.5 remain unclear. The present study was designed to examine the effect of puerarin on PM2.5-induced VSMCs proliferation, and to explore the p38 mitogen-activated protein kinase (p38 MAPK) signal mechanism involved. Methods VSMCs viability was measured by CCK-8 assay, VSMCs proliferation was assessed by BrdU immunofluorescence, the levels of superoxide dismutase (SOD) and malonaldehyde (MDA) were assayed by colorimetric assay kits, the levels of nitric oxide (NO) and endothelin-1 (ET-1) were determined by nitrate reductase method and radioimmunoassay, the levels of vascular cell adhesion molecule-1 (VCAM-1), interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) were measured by ELISA. The protein expressions of phospho-p38 MAPK (p-p38 MAPK) and proliferating cell nuclear antigen (PCNA) in the VSMCs were subjected by Western blot. Results Compared to the PM2.5-treated cells, in addition to inhibiting the PM2.5-induced VSMCs proliferation, puerarin also down-regulated the protein expressions of p-p38 MAPK and PCNA, decreased the levels of ET-1, VCAM-1, IL-6, TNF-α and MDA, increased the levels of NO and SOD. Moreover, the anti-proliferative effects of puerarin were significantly enhanced by the co-incubation of puerarin with SB203580, a selective inhibitor of p38 MAPK, as compared to the puerarin-treated cells. Conclusion These results suggest that puerarin might suppress the PM2.5-induced VSMCs proliferation via the inhibition of the p38 MAPK signaling pathway.